Seasons and pediatric dermatoses: a cross-sectional observational study in an urban skin hospital - Horatti, Laxmi B.; N. R., Kumar Dilip; Shashikiran, A. R. (International Journal of Research in Dermatology, 2021)
Background: It is a well-known that climatic conditions and seasonal variation have a direct effect on skin and the prevalence of certain skin diseases change directly with changing seasons. The presence of certain skin diseases in children reflect the status of health, hygiene and personal cleanliness of the society. The aim of the study was to know the prevalence of various skin conditions in different seasons. Methods: All fresh cases of children under 12 years of age attending the skin OPD were recorded and were divided based on the three seasons i.e.; summer winter and rainy. The results were statistically evaluated. Results: The top six conditions of our study were impetigo, miliaria, pityriasis alba, scabies, xerosis and papular urticaria. Impetigo and miliaria were more common during summer season, xerosis during winter season and scabies during rainy season. Conclusions: Different climatic conditions have varied effect on the skin and may lead to various dermatoses. To effectively corelate between seasons and skin conditions more such extensive studies on different population and ethnic groups have to be conducted.